CLINICAL FEATURES OF GOUT IN WOMEN: THE RESULTS OF A COMPARATIVE STUDY - M. S. Eliseev; N. A. Chikalenkova; V. G. Barskova (Научно-практическая ревматология)
Objective. To identify the clinical features of gout in women. Material and methods. A cross-sectional, comparative, multicenter study included 340 patients with gout (289 males and 51 females) who had been examined at V.A. Nasonova Research Institute of Rheumatology of the Russian Academy of Medical Sciences and at the Main Clinical Hospital of the Russian Interior Ministry Troops from 2002 to 2009. The main group was comprised of females; the comparison group consisted of males. The mean age of females was 52.3 ± 11.4 years; the mean age of males was 52.3 ± 10.4 years; the median duration of disease [25th; 75th per- centiles] was 4.8 [2.0; 7.6] years in females and 5.9 [3.3; 11,5] years in males (p=0.0053). Results. In the group of females, the median duration of the first arthritis attack was 14 [10; 20] days; in the compari- son group, it was 10 [7; 14] days (p=0.0014). Chronic arthritis was observed in 66.7% of females and in 31.8% of males (p<0.0001); it progressed faster in females. The median number of the joints affected during the disease was 12 [7; 17] in females, and 7 [4; 12] in males (p=0.00025). Tophi developed earlier in females than in males (the median duration of disease, before they occurred, was 3 [2; 7] and 6 [4; 10], respectively; p=0.00036). The number of tophi was greater (the median 5 [3; 8] and 2 [1; 6], respectively; p=0.0066). Females were diagnosed with type 2 diabetes mellitus (DM) (p=0.021) and chronic kidney disease (p<0.0001) more often than males; a higher serum cholesterol level (p=0.022) was observed. Females received diuretics (57% vs. 20%; p<0.0001) more often than males; however, they consumed alcoholic beverages less frequently (57 and 20%; p<0.0001; 28 and 4%; p<0.0001; respectively). Conclusion. In females, gout progression is more severe; females were diagnosed with type 2 diabetes mellitus and chronic kidney disease more frequently than males; they also had a higher cholesterol level. Females were more likely to administer diuretics and consume less alcohol.